Dietary Fatty Acids Sustain the Growth of the Human Gut Microbiota - Agans, Richard; Gordon, Alex; Kramer, Denise Lynette; Pérez-Burillo, Sergio; Rufián-Henares, José Ángel; Paliy, Oleg (American Society for Microbiology, 2018)
While a substantial amount of dietary fats escape absorption in the human small intestine and reach the colon, the ability of resident microbiota to utilize these dietary fats for growth has not been investigated in detail. In this study, we used an in vitro multivessel simulator system of the human colon to reveal that the human gut microbiota is able to utilize typically consumed dietary fatty acids to sustain growth. Gut microbiota adapted quickly to a macronutrient switch from a balanced Western diet-type medium to its variant lacking carbohydrates and proteins. We defined specific genera that increased in their abundances on the fats-only medium, including Alistipes, Bilophila, and several genera of the class Gammaproteobacteria. In contrast, the abundances of well-known glycan and protein degraders, including Bacteroides, Clostridium, and Roseburia spp., were reduced under such conditions. The predicted prevalences of microbial genes coding for fatty acid degradation enzymes and anaerobic respiratory reductases were significantly increased in the fats-only environment, whereas the abundance of glycan degradation genes was diminished. These changes also resulted in lower microbial production of shortchain fatty acids and antioxidants. Our findings provide justification for the previously observed alterations in gut microbiota observed in human and animal studies of high-fat diets.
Keywords: Nutrición; Western diet; Dietary fats; Microbial digestion; Microbiota; Nutrition